MUC4 enhances gemcitabine resistance and malignant behaviour in pancreatic cancer cells expressing cancer-associated short O-glycans. (10th April 2021) - Sagar, Satish; Leiphrakpam, Pramila D.; Thomas, Divya; McAndrews, Kyle L.; Caffrey, Thomas C.; Swanson, Benjamin J.; Clausen, Henrik; Wandall, Hans H.; Hollingsworth, Michael A.; Radhakrishnan, Prakash
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is highly lethal. MUC4 (mucin4) is a heavily glycosylated protein aberrantly expressed in PDAC and promotes tumorigenesis via an unknown mechanism. To assess this, we genetically knocked out (KO) MUC4 in PDAC cells that did not express and did express truncated O-glycans (Tn/STn) using CRISPR/Cas9 technology. We found that MUC4 knockout cells possess less tumorigenicity in vitro and in vivo, which was further reduced in PDAC cells that express aberrant overexpression of truncated O-glycans. Also, MUC4 KO cells showed a further reduction of epidermal growth factor receptors (ErbB) and their downstream signaling pathways in truncated O-glycan expressing PDAC cells. Tn-MUC4 specific 3B11 antibody inhibited MUC4-induced ErbB receptor and its downstream signaling cascades. MUC4 knockout differentially regulates apoptosis and cell cycle arrest in branched and truncated O-glycan expressing PDAC cells. Additionally, MUC4 KO cells were found to be more sensitive to gemcitabine treatment. They possessed the upregulated expression of hENT1 and hCNT3 compared to parental cells, which were further affected in cells with aberrant O-glycosylation. Taken together, our results indicate that MUC4 enhances the malignant properties and gemcitabine resistance in PDAC tumors that aberrantly overexpress truncated O-glycans via altering ErbB/AKT signaling cascades and expression of nucleoside transporters, respectively. Highlights: MUC4 alter in vitro and in vivo tumorigenic properties of truncated O-glycan expressing PDAC cells via ErbB/AKT signaling. mAb 3B11 binds with aberrant glycoforms of MUC4 (Tn/STn-MUC4) and diminishes ErbB mediated oncogenic signaling. MUC4 alter drug sensitivity in truncated O-glycan expressing PDAC via nucleoside transporters.